FRI0453 Clinical and therapeutic characterization of a colombian cohort with spondyloarthropathies. (15th June 2017) - Alzate, MA; Ramirez, F; Vargas, F; Hernandez-Parra, D; Salazar-Uribe, JC; Ortiz-Salazar, P; Pineda, R; ,
Abstract : Background: Spondyloarthropathies (SpAs) are a group of auto-inflammatory diseases, with overlapping symptoms, that include ankylosing spondylitis (AS), psoriatic arthritis (PsA), undifferentiated spondyloarthritis (Und SpA), enteropathic arthritis, and reactive arthritis (1). Objectives: To characterize the disease in a large Colombian cohort with SpAs, assessing differences in its classification, clinical manifestations, laboratory results, radiographic changes, and treatment, according to the type of SpA. Methods: A cross-sectional study was conducted in 621 patients with SpAs, in whom sociodemographic, clinical and therapeutic characteristics were analyzed based on the type of diagnosis. Statistical association was examined by means of Chi-square tests, Fisher's exact test, Mann-Whitney test, and logistic regression analyses. In all cases, a p value <0.05 was considered significant. Results: Out of the 621 patients included, AS was observed in 54, 7%, PsA in 35, 7%, and Und SpA in 9, 5%. AS was positively associated to male gender (OR 2.05 95%IC 1.5–2.8), younger age at onset, axial involvement (OR 23.2 95%IC 15.2–35.5), uveitis (OR 3.8 95%IC 2.25–6.57), radiographic sacroilitis (OR 6.95 95%IC 3.02–16.02), and HLA-B27 positivity (OR 2.3 95%IC 1.5- 3.5). PsA was associated to female gender, older age at onset, arthritis, and peripheral involvement. According to the therapeutic approach, more use of conventional DMARD therapy was found in PsA and Und SpA, while more use of biology therapy in AS. Conclusions: To our knowledge, this is the larger existing cohort with SpAs in Colombia. Understanding the natural history of disease is important to do an early diagnosis and treatment that could prevent irreversible disability. References: Ehrenfeld M. Spondyloarthropathies. Best Pract Res Clin Rheumatol. 2012;26(1):135–45. Acknowledgements: None. Disclosure of Interest: None declared